Quizlet's Usefulness for Vocabulary Learning: Perceptions of High-Level and Low-Level Chinese College EFL Learners - Pan, Huanting; Rokiah, Paee; Roslan, Ali (IJISRT, 2024)
This study investigates the perceived usefulness of Quizlet for vocabulary learning among Chinese college EFL learners and examines differences in perceptions between high-level and low-level learners based on their post-test scores. A descriptive research design was employed, utilizing a web-based survey to gather quantitative data from 95 students in Shandong province, China, after an 8-week intervention using Quizlet. The survey was based on the Technology Acceptance Model (TAM) and focused on perceived usefulness. The findings reveal that overall, students hold a positive attitude towards Quizlet, with an overall mean score of 3.81 (SD = 0.64), indicating its perceived utility in enhancing vocabulary acquisition. Specifically, Quizlet was found to be particularly beneficial for improving both receptive (M=4.18, SD=0.70) and productive (M=4.17, SD=0.68) vocabulary knowledge. However, its perceived usefulness in improving broader language skills such as reading, writing, speaking, and listening was comparatively lower. An independent samples t-test indicated no significant difference in the overall perceived usefulness between high-level and lowlevel learners, though high-level learners perceived greater benefits in learning speed and productive vocabulary knowledge. These insights suggest that while Quizlet is a valuable tool for vocabulary learning, its integration should be complemented with other methods to address comprehensive language development. The study’s implications highlight the need for tailored instructional strategies to optimize digital tools like Quizlet across different proficiency levels in EFL contexts.